Fluorinated solvent electrolyte suitable for silicon-based negative electrode, preparation method and application thereof
Through the synergistic effect of new fluorinated solvents, lithium salts and acid anhydrides, a stable SEI film is formed, which solves the electrolyte decomposition problem caused by volume effect of silicon carbon negative electrode materials, improves the life and safety of lithium-ion batteries, and is suitable for multiple Lithium-ion battery system.
Patent Information
- Application Number
- CN202310810025.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-14
AI Technical Summary
The silicon-carbon negative electrode material decomposes the electrolyte due to volume effects in lithium-ion batteries, affecting the battery life and safety. The existing fluorine solvents are reduced and decomposed at low potential to produce HF, destroying the positive electrode structure and reacting with silicon-carbon, causing the battery to deteriorate.
The new fluorine solvent is used to combine with new lithium salts and acid anhydride additives to reduce the LUMO energy level of the electrolyte by fluorine atoms to form a SEI film that is both flexible and rigid. The new lithium salt captures trace amounts of water through hydrogen bonds, and the acid anhydride captures HF. Improve the stability of the electrolyte.
It forms a SEI film with good mechanical properties, reduces electrolyte decomposition, extends battery life, improves battery structure stability and safety, and is suitable for high voltage systems.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical field:
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a fluorinated solvent electrolyte suitable for a silicon-carbon negative electrode and an application thereof. Background technology:
[0002] Compared with conventional graphite anodes, silicon-carbon anode materials have ultra-high theoretical specific capacity and low lithium desorption potential. As the market's requirements for lithium-ion battery energy density gradually increase and high-nickel systems gradually mature, upgrading the graphite anode system to a silicon-based anode system has become the main direction. However, due to the huge volume effect of silicon or silicon oxide, it is often impossible to form a stable solid electrolyte interface film on the electrode surface, which in turn causes the electrolyte to continue to decompose, leading to deterioration of the battery system, life decay, and even safety accidents. Although some fluorinated solvents have been reported as additives that can form a relatively stable interface film on the silicon-carbon surface to avoid continuous decomposition of the electrolyte, the HF produced by the reduction and decomposition of fluorinated solvents at low potentials not only destroys the positive electrode crystal structure, but also reacts with Si or SiOx in silicon-carbon to deteriorate the battery. Therefore, the development of electrolytes suitable for silicon-carbon systems is the key to achieving battery upgrades.
[0003] To solve the above problems, the main measures currently adopted are: (1) Fluorinated carbonates are used as electrolyte additives to improve the mechanical properties of the negative electrode surface interface film and reduce the continuous decomposition of the electrolyte and the loss of active lithium. For example: Chinese invention patent CN202210798099.9 uses one or both of 3,3,3-trifluoropropylene carbonate and fluoroethylene carbonate as additives, and utilizes the strong electron-withdrawing ability of fluorine atoms to preferentially reduce the silicon-carbon negative electrode surface to generate a stable, rigid and flexible SEI layer, thereby achieving long-term stable cycle of the battery; (2) Through the design of the binder, the silicon-carbon negative electrode is tightly bonded together to avoid material pulverization due to volume expansion during lithium insertion and extraction, thereby causing electrolyte decomposition. For example: Chinese invention patent CN202010522606.7 provides a mussel biomimetic polymer binder with strong hydrophobicity, which has both carboxyl and flexible structures in its structure. While enhancing the binding force between the silicon-carbon negative electrode material and the silicon-carbon negative electrode active material, it also restrains and alleviates the volume expansion of the silicon-carbon negative electrode active material, prevents the silicon-carbon negative electrode active material from pulverizing, and improves the cycle performance of the resulting silicon-carbon negative electrode material, negative electrode and lithium-ion battery.
[0004] The present invention uses a new fluorinated solvent in combination with a new lithium salt and anhydride additives. The fluorine atoms in the fluorinated solvent reduce the LUMO energy level of the electrolyte, so that a SEI membrane component with both flexibility and rigidity is formed before the lithium insertion potential, thereby avoiding continuous decomposition of the electrolyte due to material expansion or dissolution of the SEI membrane during the charge and discharge process. In addition, the anions in the new lithium salt also have a lower LUMO energy level. According to their dosage, the organic and inorganic composition in the SEI membrane can be adjusted to obtain a SEI membrane with good mechanical properties. At the same time, the new lithium salt can capture trace water in the electrolyte through hydrogen bonds to improve the stability of the electrolyte. The anhydride additive can capture HF generated by the reduction of the fluorinated solvent to form a weaker acid, which is captured by the new lithium salt, thereby improving the structural stability of the material. Summary of the invention:
[0005] In view of the gas generation problem faced by silicon-based anode lithium-ion batteries using fluorinated solvents, the present invention provides a fluorinated solvent electrolyte suitable for silicon-carbon negative electrodes. This electrolyte is not only suitable for conventional ternary, lithium cobalt oxide, lithium iron phosphate, lithium titanate and other systems, but also can be applied to high-voltage systems such as layered lithium-rich positive electrodes due to its strong oxidation resistance.
[0006] In order to achieve the synergistic effect of fluorinated solvents, new lithium salts and additives and ensure the uniformity of structural stability, life and safety of silicon-based negative electrode lithium-ion batteries, the present invention adopts the following technical solutions:
[0007] On the one hand, the present invention provides a fluorinated solvent electrolyte suitable for a silicon-carbon negative electrode, wherein the electrolyte comprises a fluorinated organic solvent, a new lithium salt, lithium hexafluorophosphate, and an additive.
[0008] In the present invention, the fluorinated organic solvent is selected from one or more of fluoroethylene carbonate, bisfluoroethylene carbonate, 3,3,3-trifluoropropylene carbonate, methyl trifluoroethyl carbonate, and di(2,2,2-trifluoroethyl) carbonate. In terms of weight percentage, the fluorinated organic solvent accounts for 75% to 90% of the mass of the electrolyte. It is preferably a mixture of one or more of fluoroethylene carbonate, bisfluoroethylene carbonate, and 3,3,3-trifluoropropylene carbonate and one or two of methyl trifluoroethyl carbonate and di(2,2,2-trifluoroethyl) carbonate. It is preferably that one or more of fluoroethylene carbonate, bisfluoroethylene carbonate, and 3,3,3-trifluoropropylene carbonate accounts for 15% to 30% of the total mass of the electrolyte, and one or two of methyl trifluoroethyl carbonate and di(2,2,2-trifluoroethyl) carbonate accounts for 55% to 65% of the total mass of the electrolyte.
[0009] In the present invention, the novel lithium salt is one or both of 2-trifluoromethyl-4,5-dicyanoimidazole lithium and 2-perfluoroethyl-4,5-dicyanoimidazole lithium, accounting for 3% to 10% of the total mass of the electrolyte. The structural formula of the novel lithium salt is as follows:
[0010]
[0011] In the present invention, the lithium hexafluorophosphate accounts for 3% to 10% of the total mass of the electrolyte.
[0012] In the present invention, the electrolyte additive is one or both of succinic anhydride and diglycolic anhydride. Preferably, the additive accounts for 1% to 2.5% of the total mass of the electrolyte.
[0013] On the other hand, the present invention also provides a method for preparing a fluorinated solvent electrolyte suitable for a silicon-carbon negative electrode, the method comprising the following steps:
[0014] First, a fluorinated organic solvent is prepared in a glove box with a water content of <0.01 and an oxygen content of <0.01 according to the weight ratio; secondly, a 4A molecular sieve activated at 500°C is added to the prepared fluorinated organic solvent in a ratio of 3:1 to remove water for 24 hours until the water content in the solvent is <20ppm, and the molecular sieve in the solvent is filtered using a G4 sand core funnel; then, the fluorinated organic solvent after dehydration is sealed and stored in a -20°C refrigerator for 4 hours, and the frozen fluorinated solvent is added with a new lithium salt and lithium hexafluorophosphate according to the weight ratio, and the dissolution rate is controlled during the addition process, and the temperature rise is controlled to be <5°C; finally, the additives are added to the completely dissolved electrolyte according to the ratio.
[0015] The beneficial effects of the present invention are as follows: (1) the fluorinated solvent described in the present invention can improve the oxidation resistance of the electrolyte, match the high-voltage positive electrode, and at the same time can form an organic-inorganic composite solid electrolyte interface film with good mechanical properties on the surface of the silicon-based negative electrode, thereby reducing the decomposition of the interface film caused by the volume effect of the silicon-based negative electrode and thus causing the life attenuation;
[0016] (2) The hydrogen cyanide functional group in the anion of the novel lithium salt LiTDI and LiPDI can capture trace water in the electrolyte and weak acid generated by the reaction of additives with water through hydrogen bonds, thereby preventing the fluorinated organic solvent from reacting with water at a low potential at the negative electrode to produce HF, causing the collapse of the positive and negative electrode structures. The fluorinated alkyl group in the anion can improve the oxidation resistance of the anion, prevent the decomposition of the anion at a high potential, and improve the electrochemical window of the electrolyte;
[0017] (3) The additives succinic anhydride and diglycolic anhydride can combine with trace water in the electrolyte to form a weak acid, which is captured by the new lithium salt, thereby preventing the fluorinated solvent from generating more HF that affects the battery life and safety. Specific implementation method:
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Raw materials and sources: The fluorinated organic solvent, new lithium salt, lithium hexafluorophosphate, and acid anhydride additive are commercial raw materials. Before the reagents are prepared, they can only be used if the purity is > 99.9% as determined by gas chromatography and ion chromatography. Test and characterization methods:
[0020] Test method: The cycle test adopts 1C constant current and constant voltage charging, cut-off voltage 4.8V, cut-off current 0.05C, and discharge adopts constant current discharge, and the discharge current is 1C; the gas production is measured by the water displacement method, and the acidity is calculated by titration with triethylamine acetonitrile solution and methyl orange as the indicator.
[0021] Example 1
[0022] The weight ratio of each component of the electrolyte is: 10% of bis(fluoroethylene carbonate), 35% of methyl trifluoroethyl carbonate, 35% of di(2,2,2-trifluoroethyl) carbonate, 9% of lithium hexafluorophosphate, 9% of LiTDI, and 2% of succinic anhydride. The positive electrode material of the assembled soft pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0023] Example 2
[0024] The weight ratio of each component of the electrolyte is: 25% bis(fluoroethylene carbonate), 27.5% methyl trifluoroethyl carbonate, 27.5% bis(2,2,2-trifluoroethyl) carbonate, 9% lithium hexafluorophosphate, 9% LiTDI, 2% succinic anhydride, and the positive electrode material of the assembled soft pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0025] Example 3
[0026] The weight ratio of each component of the electrolyte is: 40% of bisfluoroethylene carbonate, 20% of methyl trifluoroethyl carbonate, 20% of di(2,2,2-trifluoroethyl) carbonate, 9% of lithium hexafluorophosphate, 9% of LiTDI, and 2% of succinic anhydride. The positive electrode material of the assembled soft pack battery is Li[Li 1 / 3 Mn 2 / 3]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0027] Example 4
[0028] The weight ratio of each component of the electrolyte is: 25% of bis(3,3-trifluoropropylene carbonate), 30% of methyl trifluoroethyl carbonate, 30% of bis(2,2,2-trifluoroethyl) carbonate, 3% of lithium hexafluorophosphate, 10% of LiTDI, and 2% of succinic anhydride. The positive electrode material of the assembled soft pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0029] Example 5
[0030] The weight ratio of each component of the electrolyte is: 25% of bis(3,3-trifluoropropylene carbonate), 30% of methyl trifluoroethyl carbonate, 30% of bis(2,2,2-trifluoroethyl) carbonate, 8% of lithium hexafluorophosphate, 5% of LiTDI, and 2% of succinic anhydride. The positive electrode material of the assembled soft pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0031] Example 6
[0032] The weight ratio of each component of the electrolyte is: 25% of bis(3,3-trifluoropropylene carbonate), 30% of methyl trifluoroethyl carbonate, 30% of di(2,2,2-trifluoroethyl) carbonate, 10% of lithium hexafluorophosphate, 3% of LiTDI, and 2% of succinic anhydride. The positive electrode material of the assembled soft pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0033] Example 7
[0034] The weight ratio of each component of the electrolyte is: 25% of bis(3,3-trifluoropropylene carbonate), 30% of methyl trifluoroethyl carbonate, 30% of bis(2,2,2-trifluoroethyl) carbonate, 8% of lithium hexafluorophosphate, 6.5% of LiTDI, and 0.5% of succinic anhydride. The positive electrode material of the assembled soft pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0035] Example 8
[0036] The weight ratio of each component of the electrolyte is: 25% of bis(3,3-trifluoropropylene carbonate), 30% of methyl trifluoroethyl carbonate, 30% of bis(2,2,2-trifluoroethyl) carbonate, 8% of lithium hexafluorophosphate, 4% of LiTDI, and 3% of succinic anhydride. The positive electrode material of the assembled soft pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0037] Example 9
[0038] The weight ratio of each component of the electrolyte is: 25% of bis(3,3-trifluoropropylene carbonate), 30% of methyl trifluoroethyl carbonate, 30% of bis(2,2,2-trifluoroethyl) carbonate, 6% of lithium hexafluorophosphate, 4% of LiTDI, and 5% of succinic anhydride. The positive electrode material of the assembled soft pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0039] Comparative Example 1
[0040] The weight ratio of each component of the electrolyte is: ethylene carbonate 25%, ethyl methyl carbonate 27.5%, diethyl carbonate 27.5%, lithium hexafluorophosphate 9%, LiTDI 9%, succinic anhydride 2% Assembled soft pack battery The positive electrode material of the battery is Li[Li 1 / 3Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0041] Comparative Example 2
[0042] A fluorinated solvent electrolyte suitable for silicon-based negative electrode and its application, wherein the weight ratio of each component of the electrolyte is: 25% fluoroethylene carbonate, 30% methyl trifluoroethyl carbonate, 30% bis(2,2,2-trifluoroethyl) carbonate, 13% lithium hexafluorophosphate, and 2% succinic anhydride. The positive electrode material of the assembled soft-pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0043] Comparative Example 3
[0044] A fluorinated solvent electrolyte suitable for silicon-based negative electrode and its application, wherein the weight ratio of each component of the electrolyte is: 25% fluoroethylene carbonate, 30% methyl trifluoroethyl carbonate, 30% di(2,2,2-trifluoroethyl) carbonate, 10% lithium hexafluorophosphate, and 5% LiTDI. The positive electrode material of the assembled soft-pack battery is Li[Li1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0045] Comparative Example 4
[0046] A fluorinated solvent electrolyte suitable for silicon-based negative electrode and its application, wherein the weight ratio of each component of the electrolyte is: 25% fluoroethylene carbonate, 30% methyl trifluoroethyl carbonate, 30% di(2,2,2-trifluoroethyl) carbonate, 4% lithium hexafluorophosphate, 5% LiTDI, 6% succinic anhydride, and the positive electrode material of the assembled soft-pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, with a specific capacity of 280mAh / g, and the negative electrode is silicon oxygen carbon, with a specific capacity of 600mAh / g.
[0047] Comparative Example 5
[0048] A fluorinated solvent electrolyte suitable for silicon-based negative electrode and its application, wherein the weight ratio of each component of the electrolyte is: 25% fluoroethylene carbonate, 30% methyl trifluoroethyl carbonate, 30% di(2,2,2-trifluoroethyl) carbonate, 12% lithium hexafluorophosphate, 1% LiTDI, 2% succinic anhydride, and the positive electrode material of the assembled soft-pack battery is Li[Li 1 / 3 Mn 2 / 3 ]O2, specific capacity 280mAh / g, negative electrode is silicon oxygen carbon, specific capacity is 600mAh / g. Table 1 shows the battery capacity retention rate and volume expansion rate of Examples 1 to 9 and Comparative Examples 1 to 5 after 300 cycles
[0049]
[0050]
[0051] Table 2 Acidity of electrolyte obtained by centrifugation for 10 cycles in Example 1 to Example 9 and Comparative Example 1 to Comparative Example 5
[0052] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 acidity 55.8 45.6 52.8 65.4 50.2 53.9 55.7 40.3 44.2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 acidity 60.2 128.6 129.7 74.9 80.3
Claims
1. An electrolyte, characterized in that: The electrolyte comprises a fluorinated organic solvent, a novel lithium salt, Lithium hexafluorophosphate, additive.
2. The electrolyte according to claim 1, characterized in that The fluorinated organic solvent is selected from one or more of fluoroethylene carbonate, difluoroethylene carbonate, 3,3,3-trifluoropropylene carbonate, methyl trifluoroethyl carbonate, and di(2,2,2-trifluoroethyl) carbonate. In terms of weight percentage, the fluorinated organic solvent accounts for 75% to 90% of the mass of the electrolyte.
3. The electrolyte according to claim 2, characterized in that The fluorinated organic solvent is preferably one or more of fluoroethylene carbonate, difluoroethylene carbonate, 3,3,3-trifluoropropylene carbonate and methyl trifluoroethyl carbonate, two (2,2,2-trifluoroethyl) carbonate or a mixture of two thereof, the One or more of fluoroethylene carbonate, difluoroethylene carbonate, and 3,3,3-trifluoropropylene carbonate account for 15% to 30% of the total mass of the electrolyte, and the methyl trifluoroethyl carbonate, One or two of di(2,2,2-trifluoroethyl) carbonates account for 55% to 50% of the total mass of the electrolyte. 65%。 4. The electrolyte according to any one of claims 1 to 3, characterized in that The novel lithium salt is one or both of 2-trifluoromethyl-4,5-dicyanoimidazole lithium and 2-perfluoroethyl-4,5-dicyanoimidazole lithium, preferably accounting for 3% to 10% of the total mass of the electrolyte.
5. The electrolyte according to any one of claims 1 to 4, characterized in that The lithium hexafluorophosphate accounts for 3% to 10% of the total mass of the electrolyte.
6. The electrolyte according to any one of claims 1 to 5, characterized in that The electrolyte additive is one or both of succinic anhydride and diglycolic anhydride. Preferably, the additive accounts for 1% to 2.5% of the total mass of the electrolyte.
7. The method for preparing an electrolyte according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) preparing a fluorinated organic solvent in a glove box with a water content of less than 0.01 and an oxygen content of less than 0.01 according to the weight ratio; (2) adding 4A molecular sieves activated at 500° C. to the prepared fluorinated organic solvent in a ratio of 3:1 to remove water for 24 hours until the water content in the solvent is less than 20 ppm, and filtering the molecular sieves in the solvent with a G4 sand core funnel; (3) sealing the fluorinated organic solvent after dehydration and storing it in a -20° C. refrigerator for 4 hours, adding a new lithium salt and lithium hexafluorophosphate to the frozen fluorinated solvent in the weight ratio, controlling the dissolution rate during the addition process and controlling the temperature rise to less than 5° C.; (4) adding additives to the solution obtained in step (3) to obtain an electrolyte.
8. Use of the electrolyte according to any one of claims 1 to 6 or the electrolyte prepared by the preparation method according to claim 7 as an electrolyte for a battery containing a silicon-carbon negative electrode.
Citation Information
Patent Citations
Mussel biomimetic polymer, silicon-carbon negative electrode binder, silicon-carbon negative electrode material and application
CN113773435A
Electrolyte for silicon-carbon system lithium ion battery
CN115172873A